2020
DOI: 10.3390/ijerph17197258
|View full text |Cite
|
Sign up to set email alerts
|

Does Motivation in Physical Education Have an Impact on Out-of-School Physical Activity over Time? A Longitudinal Approach

Abstract: Previous research based on the trans-contextual model proposes that autonomous motivation in physical education (PE) is transferable to an out-of-school leisure-time (LT) context. However, only cross-sectional and unidirectional analyses have been conducted. The present study used a longitudinal design assessing N = 1681 students (M = 14.68 years) on two occasions, measuring the following constructs: perceived need for support in PE, motivational regulation during PE and LT, attitude, subjective norm, perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 59 publications
(90 reference statements)
5
22
0
6
Order By: Relevance
“…Namely, autonomous motivation for PA in PE predicted autonomous motivation in leisure time. This finding is in line with Vallerand's (11) theory that autonomous forms of motivation in one context are linked to autonomous motivation for the same kind of behavior in similar contexts and confirmed by empirical evidence (32). These similar but distinct constructs are related when behavior is autonomous in a certain context and subsequently creates motivational representations and anticipated patterns of action in that context that serve as a useful template for motivation and action in closely related contexts (25).…”
Section: Direct Trans-contextual Linkssupporting
confidence: 87%
See 2 more Smart Citations
“…Namely, autonomous motivation for PA in PE predicted autonomous motivation in leisure time. This finding is in line with Vallerand's (11) theory that autonomous forms of motivation in one context are linked to autonomous motivation for the same kind of behavior in similar contexts and confirmed by empirical evidence (32). These similar but distinct constructs are related when behavior is autonomous in a certain context and subsequently creates motivational representations and anticipated patterns of action in that context that serve as a useful template for motivation and action in closely related contexts (25).…”
Section: Direct Trans-contextual Linkssupporting
confidence: 87%
“…Specifically, higher perceived support for autonomy in PE was directly and positively related to needs satisfaction, which, in turn, was directly and positively related to autonomous motivation in PE. The findings of another recent study revealed that needs for autonomy, competence and relatedness satisfaction were positively related to autonomous motivation (32). Meanwhile, autonomous motivation in PE, which represented contextual motivation in the model, was further related positively to situational motivation, as represented by intention in PE, which is in line with the theoretical presumption that situational motivation is defined by contextual motivation (25).…”
Section: Direct Relationships Within the Physical Education Domainsupporting
confidence: 79%
See 1 more Smart Citation
“…Hutmacher, Eckelt, Bund, and Steffgen [ 25 ] performed a longitudinal study on 1681 students from elementary and high school in the context of PE. The measured variables were perceived need for support in PE, motivational regulation during PE, leisure time, attitude, subjective norm, perceived behavioral control, intention, and physical activity behavior.…”
Section: The Studies Includedmentioning
confidence: 99%
“…Although the 3-part TCM questionnaire battery has not yet been translated or cross-culturally adapted to the Danish educational context for use within the 11 for Health concept, the model's effect patterns have been supported by earlier cross-cultural adaptational research involving persons of different ages, and with different cultural and national backgrounds (Barkoukis et al, 2010;Hagger, 2014;Hagger et al, 2003Hagger et al, , 2005Hutmacher et al, 2020;Müftüler & İnce, 2015;Shen et al, 2008). In order to investigate the motivational processes during participation in the 11 for Health concept, the authors, therefore, had to translate and culturally adapt the 3-part TCM questionnaire battery into a web-based questionnaire battery to be used within the school-based 11 for Health concept.…”
Section: Introductionmentioning
confidence: 99%